Kajian pengelolaan sampah rumah tangga (SRT) dan sampah sejenis sampah rumah tangga (SSRT)) di Kabupaten Teluk Bintuni - Nicolas Riruma; Nurhaida Sinaga; Marlyn N. Lekitoo (Program Pascasarjana Universitas Papua, 2021)
The objectives to be achieved from this research are to determine the amount of waste generation and characteristics, evaluate waste management in 2019, project a waste balance for 2020-2025, and identify the form of waste management policies, strategies and programs for 2020-2025 in Teluk Bintuni Regency. The results of the study, the amount of waste generation was 3.46 l / o / h; composition of organic waste 67.12%, plastic waste 26.30%, and other inorganic waste 6.75%; managed waste 65.55%; served population 76.90%; implementation of operational technical standards 45.43%; effectiveness of the role of local government 39.49% (less effective criteria); low community behavior in waste management (69%), community perception in good waste management (81%); projected waste balance for 2020-2025 waste generation 169,229.79 tons, 30% reduction target (44,427 tonnes), 70% handling target (122,596 tonnes), 100% managed waste by 2025 (169,229.79 tonnes); 2 forms of policies, 6 strategies and 17 waste management programs were identified for 2020-2025.